2021
DOI: 10.1016/j.numecd.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and the Covid-19 pandemic: Three factors with high impact on community health

Abstract: Aims In the course of the COVID-19 pandemic, multiple suggestions have been delivered through websites and social media referring to natural substances and various kinds of supplements with thaumaturgical properties in preventing and/or fighting the coronavirus infection. Indeed, there is no clinical trial evidence that a dietary or pharmacological supplementation of any particular substance will increase the effectiveness of the immune defences. There are however three nutritional issues that des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…During the COVID-19 pandemic, the influence of social isolation and lockdowns on eating patterns should not be ignored, as it has already had acute impacts and will most likely have long-term negative consequences for public health. Poor dietary habits that are continued over time will increase plasma risk factors for cardiovascular disease, diabetes, and cancer [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the influence of social isolation and lockdowns on eating patterns should not be ignored, as it has already had acute impacts and will most likely have long-term negative consequences for public health. Poor dietary habits that are continued over time will increase plasma risk factors for cardiovascular disease, diabetes, and cancer [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Butler and Barrientos (2020) suggested that highly processed diets composed of high fat and carbohydrate content, low fiber foods may play a significant role in not only association with risk factors but also with negative impacts on innate and adaptive immunological function ( 46 ). Excessive dietary sodium and alcohol in addition to deficiencies in vitamin D may also negatively predispose an individual to be at greater risk for infection and greater severity of the disease ( 47 ). Yet, Downer, Berkowitz, Harlan, Olstad, and Mozaffarian, et al (2020) suggest that targeted nutritional interventions have a significant role in the treatment, prevention, management, and reversal of some diseases ( 48 ).…”
Section: Nutrition In Covid-19 Rehabilitationmentioning
confidence: 99%